ESTIMASI TINGKAT RISIKO INVESTASI EMAS MENGGUNAKAN PENDEKATAN GENERALIZED EXTREME VALUE DAN GENERALIZED PARETO DISTRIBUTION - Noviana Pratiwi; Catur Iswahyudi (Journal of Fundamental Mathematics and Applications (JFMA), 2019)
This study estimates the level of risk in investing in gold. Value at Risk (VaR) is a method which can be used for calculating the level of risk. There are two distribution approaches used, namely Generalized Extreme Value Distribution (GEV) and Generalized Distribution Pareto (GDP). These two distributions are used because gold data is alleged to have a heavy tail distribution. The study uses secondary data on gold prices with January 2015 to December 2017 period with a total of 876 data. The results obtained indicate that the data return for the gold price has a heavy tail. Estimation results obtained indicate that the VaR value at the 95% confidence level is less than VaR with a 99% confidence level so it can be concluded that the higher the level of risk to be taken, the greater the level of confidence and capital allocation to cover losses taken by investors. The GDP Estimation value gives a greater value than GEV. and the largest VaR value is shown at 4.049%, which means that the maximum loss that may occur in one period ahead is 4.049%.